Bond Strength of Bar Using Grouting for Precast Concrete Connection - Anis Rosyidah; I Ketut Sucita; Praganif Sukarno; S. R. Permita Sari; Chintya Sari (Applied Research on Civil Engineering and Environment (ARCEE), 2019)
In precast concrete, a connection is needed to unite the components so that they become a whole unified structure. This study aims to determine the reinforcement strength and length of reinforcement in precast concrete connections. To paste reinforcement into precast concrete, giving additional material in the form of grouting which is called sika grout 215 and functions as an adhesive is necessary. Pullout testing is carried out in the laboratory, and its simulation by modeling uses the finite element method based software. This research is divided into 2 phases. The first phase is making specimen to examine the bond strength between the concrete and reinforcement that has been given sika grout 215. So monolithic specimen is made as a comparison. The result of the bond strength of the monolithic test specimen is 6.24 MPa, and the sika grout 215 category is 6.52 MPa. From the experimental results in the laboratory with modeling, it is obtained the bond strength ratio of 0.94. The length of development (ld) based on the results of the testing phase I of 200 mm. The second phase is examining the damage pattern due to the stress that occurred. Specimens are made into 4 categories, namely modeling developments with the length of 120 mm (<40% ld), with the length of 160 mm (<20% ld), with length of 200 mm (= ld), and with the length of 260 mm (> 30% ld) both for monoliths and sika grout 215. The damage pattern, which is in the form of yielding and breaking reinforcement as the result of the pullout experiment in the laboratory shows not much different from the result of simulation using the software.